Misconceptions in Environmental Learning: A Four-Tier Diagnostic Study in Indonesian Primary Education - Haryanto, Nathania Janani (Proceedings of Forum for University Scholars in Interdisciplinary Opportunities and Networking, 2025)
This study investigates the misconceptions held by fifth-grade elementary students in learning Natural and Social Sciences. Employing a descriptive quantitative approach, the research utilizes a Four-Tier Diagnostic Test designed to measure not only students’ conceptual understanding but also their confidence levels and reasoning behind their answers. The results reveal that 41.4% of students correctly understood the material, while 35.1% demonstrated misconceptions, and 23.2% fell into the category of not understanding. A deeper analysis indicated that students frequently chose "don’t know" as a justification, especially on items requiring an understanding of the interrelationship between environmental factors. These findings highlight the persistence of intuitive, yet scientifically inaccurate reasoning, often stemming from daily experiences or insufficient instructional strategies. The study underscores the need for more diverse and contextual teaching methods, including visual media, collaborative discussions, and real-world environmental exploration. Such strategies are essential for correcting misunderstandings and enhancing conceptual comprehension. The diagnostic insight provided by the Four-Tier Test enables educators to design targeted and adaptive learning interventions that respond directly to the identified misconceptions. This research affirms the critical role of diagnostic assessments in improving the quality of science education at the elementary level.